Prinsip Kerja Sama dan Kesantunan Tuturan Perawat dalam Menghadapi Pasien yang Mengalami Gangguan Jiwa di Rumah Sakit Jiwa Surakarta - Rahayu, Hesti Marnahati, Prof. Dr. H.A. Ngalim, MM., M. Hum (2015)
In this study, there are two objectives to be achieved (1) To describe the shape of the principle of cooperation between the nurse and patient speech impaired people in the RSJ. Surakarta, (2) describe the manifestation of the principle of modesty in speech nurses in the face of patients with mental disorders in the RSJ. Surakarta. This research uses descriptive method using a qualitative approach in the form of qualitative research using content analysis research strategy. Methods and techniques used in data collection in this study is the record, see and record. Methods of data analysis using a unified, unified method used is a method of determining tool frontier pragmatic people who become dialogue partner. Results showed from 33 the data collected, speech containing maxim of quantity (the maxim of quantity) amounted to 1 speech, maxim of quality (the maxim of quality) amounted to 1 speech, maxims relevance (the maxim of relevance) amounted to 8 speech, and maxims implementation (the maxim of Manner) amounted to 1 speech. Meanwhile, from 22 the data politeness maxims found wisdom (tact maxim), as many as 3 data. Maksim philanthropy (generosity maxim, as much as 3 data. Maksim award (approbation maxim), as many as 10 data. Maksim simplicity (modesty maxim), 2 data. Maksim agreement (agreement maxim), as many as 3 data. And found 1 Data maxim kesimpatisan (sympath maxim).